TKI Maintenance After Stem-Cell Transplantation for FLT3-ITD Positive Acute Myeloid Leukemia: A Systematic Review and Meta-Analysis - Gagelmann, Nico; Wolschke, Christine; Klyuchnikov, Evgeny; Christopeit, Maximilian; Ayuk, Francis; Kröger, Nicolaus (Frontiers in Immunology, 2021)
This analysis aimed to systematically review and synthesize the existing evidence regarding the outcome of tyrosine kinase inhibitor (TKI) maintenance therapy after allogeneic stem-cell transplantation for patients with FLT3-ITD-mutated acute myeloid leukemia (AML). We searched publicly available databases, references lists of relevant reviews, registered trials, and relevant conference proceedings. A total of 7 studies comprising 680 patients were included. Five studies evaluated sorafenib and 2 studies evaluated midostaurin, compared with control. The incidence of relapse was significantly reduced after TKI therapy, showing an overall pooled risk ratio (RR) of 0.35 (95% confidence interval [CI], 0.23-0.51; P<0.001), with a marked 65% reduced risk for relapse. The overall pooled RR for relapse-free survival and overall survival showed significantly improved outcome after TKI maintenance therapy, being 0.48 (95% CI, 0.37-0.61; P<0.001) and 0.48 (95% CI, 0.36-0.64; P<0.001). The risk for relapse or death from any cause was reduced by 52% using TKI. No difference in outcome was seen for non-relapse mortality, and the risk for chronic or acute graft-versus-host disease appeared to be increased, at least for sorafenib. In conclusion, posttransplant maintenance therapy with TKI was associated with significantly improved outcome in relapse and survival in patients with FLT3-ITD positive AML.